"The Wolf's Dictionary": Confronting the Triumph of a Predatory World View. Issue 4 (2nd October 2017) - Benjamin, Jessica
Abstract: In this article the author draws connections between the current political situation in the United States and other historical moments in which mass movements with authoritarian tendencies played a significant role. Her thesis is that psychoanalytic thinking can contribute to understanding this profoundly anti-democratic constellation in terms of the core fantasy of "only one can live." This fantasy supports the polarity between Them and Us, in which a discardable, devalued subjugated group is seen to be a threat to the self-proclaimed dominant group. She argues that, historically, the United States has been riven by the contradiction between the democratic values of equality and social solidarity and the ideology that tries to justify harming others in the name of self-preservation, not only in slavery but also in the capitalist system of extracting profit from others' labor. The latest version of this anti-democratic ideology, neoliberalism, has colluded in denying the harm being done to our nominal democracy, or to the many, by the oligarchic concentration of power in the hands of the wealthy who profit from this system. She aims to elucidate the psychic forces that enable the dissociation of this harming and those that might contribute to exposing the threat to democracy and, through acknowledging the history of harming, engage in repair.